Dogma in medieval Jewish thought : from Maimonides to Abravanel - Kellner, Menachem Marc, 1946- (Littman library of Jewish civilization (Series), 2004)
Dogma in Medieval Jewish Thought is an essay in the history of ideas which traces the development of creed formation in Judaism from its inception with Moses Maimonides (1138-1204) to the beginning of the sixteenth century when systematic attention to the problem disappeared from the agenda of Jewish intellectuals. The dogmatic systems of Maimonides, Duran, Crescas, Albo, Bibago, Abravanel, and a dozen lesser-known figures are described, analysed, and compared. Relevant texts are presented in English translation. For the most part these are texts which have never been critically edited and tra.